Development and support of small innovative entrepreneurship in Europe and the USA - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Плотнікова, Марія Федорівна; Плотнікова, М. Ф.; Плотникова, Мария Федоровна; Plotnikova, Mariia F.; Нєлєпова, Альона Володимирівна; Нєлєпова, А. В.; Нелепова, Алена Владимировна; et al. (Universidad San Gregorio de Portoviejo, 2020)
Modern business practice shows that small innovative entrepreneurship needs special support in the context of rapid development of science and technology. To implement the outlined, various business support programs are being developed at a rapid pace, which are being actively implemented in practice. The aim of the article is to present the conceptual features of the development and support of small innovative entrepreneurship in Europe and the United States. The purpose of the academic paper is to present the conceptual features of supporting small innovative ntrepreneurship in Europe and the United States of America. A number of research methods have been used to reveal the purpose of the article, including such as: system-structural method, method of description, method of theoretical analysis, method of comparison, method of observation, method of synthesis, experimental method, modeling method, grouping method, generalization method. It has been proved that in European countries and the USA the policy of support of small innovative business is actively pursued. It has been found that the UK has developed and implemented Europe 2020: Scottish national reform program 2017, which provides support for small innovative businesses by promoting innovation in the business environment. It has been established that the Netherlands intends to expand opportunities to increase funding for small innovative entrepreneurships and provide favorable conditions for interaction between the private sector and scientists and researchers. It has been determined that in Germany the support of small innovative enterprises is granted by BVIZ, which provides opportunity and initiates potential entities to conduct small innovative entrepreneurship and activities in the direction of technology transfer and promotion of economic development. It has been established that in the USA support of small innovative entrepreneurships is provided by Small Business Development Centers which operate in various states of this country at local level and provide direct consulting services concerning prospects of business planning, legality (legitimacy) of activity, prospects of development of scientific researches, prospects of development of technics and technologies. It has been found that in addition to states, support for small innovative entrepreneurships is provided by international organizations and institutions, such as European Bank for Reconstruction and Development and the European Commission.

Сучасна підприємницька практика свідчить, що мале інноваційне підприємництво потребує особливої ​​підтримки в умовах стрімкого розвитку науки і техніки. Для реалізації окресленого швидкими темпами розробляються різноманітні програми підтримки бізнесу, які активно впроваджуються на практиці. Метою статті є представлення концептуальних особливостей розвитку та підтримки малого інноваційного підприємництва в Європі та США. Метою наукової роботи є представлення концептуальних особливостей підтримки малого інноваційного підприємництва в Європі та Сполучених Штатах Америки. Для розкриття мети статті використано ряд методів дослідження, серед яких: системно-структурний метод, метод опису, метод теоретичного аналізу, метод порівняння, метод спостереження, метод синтезу, експериментальний метод, моделювання. метод, метод групування, метод узагальнення. Доведено, що в країнах Європи та США активно проводиться політика підтримки малого інноваційного бізнесу. Встановлено, що у Великобританії розроблено та впроваджено програму Європа 2020: національна програма реформ Шотландії 2017, яка передбачає підтримку малого інноваційного бізнесу шляхом сприяння інноваціям у бізнес-середовищі. Встановлено, що Нідерланди мають намір розширити можливості збільшення фінансування малого інноваційного підприємництва та створити сприятливі умови для взаємодії приватного сектора з науковцями та дослідниками. Визначено, що в Німеччині підтримку малим інноваційним підприємствам надає BVIZ, яка надає можливість та ініціює потенційних суб’єктів малого інноваційного підприємництва та діяльності у напрямку трансферу технологій та сприяння економічному розвитку. Встановлено, що в США підтримку малого інноваційного підприємництва надають Центри розвитку малого бізнесу, які діють у різних штатах цієї країни на місцевому рівні та надають прямі консультаційні послуги щодо перспектив бізнес-планування, законності (легітимності) діяльності, перспектив розвитку наукових досліджень, перспектив розвитку техніки і технологій. Встановлено, що окрім держав підтримку малого інноваційного підприємництва надають міжнародні організації та установи, такі як Європейський банк реконструкції та розвитку та Європейська комісія.
Petrunenko I. Development and support of small innovative entrepreneurship in Europe and the USA / I. Petrunenko, M. Plotnikova, A. Nieliepova, T. Bilousko, A. Mazur, I. Goncharenko // Revista San Gregorio. - № 42. - Universidad San Gregorio de Portoviejo, 2020. - P. 194-204.
Keywords: small innovative entrepreneurship; projects; programs; strategy; startup; мале інноваційне підприємництво; проекти; програми; стратегія; стартап; Research Subject Categories::SOCIAL SCIENCES::Business and economics